1990
DOI: 10.1002/eqe.4290190506
|View full text |Cite
|
Sign up to set email alerts
|

Effective time‐domain soil‐structure interaction analysis based on FFT algorithm with causality condition

Abstract: SUMMARYWe propose an effective and reliable time-domain substructure technique which takes soil-structure interaction effects into account and uses the flexibility coefficients of unbounded soil obtained in the frequency domain. Compared with previous methods, the frequency points t o calculate flexibility coefficients, and computational loads in the calculation of time-domain interaction forces, are reduced.In the formulation, we have assumed the flexibility coefficient to be a periodic function, obtained wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For the purpose of preventing this, a method for computing either the real part or the imaginary part from the other part by carrying out the Hilbert transform is often used [5]. However, this method causes a distortion of the original function.…”
Section: Proposal For a New Transform Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of preventing this, a method for computing either the real part or the imaginary part from the other part by carrying out the Hilbert transform is often used [5]. However, this method causes a distortion of the original function.…”
Section: Proposal For a New Transform Methodsmentioning
confidence: 99%
“…Meek [3] showed the general version of the recursive method and Motosaka et al [4] indicated the applicability of the ARMA type recursive formula by means of developing the aforementioned method. Hayashi et al [5] investigated the formulation of the transform method using the fast Fourier transform with consideration to the causality condition.…”
Section: Introductionmentioning
confidence: 99%
“…The origins of this method date back to Wolf & Obernhuber, 1985, who developed a numerical method in the time domain in which the impulse response obtained from dynamic soil stiffness by using inverse Fourier transform was applied to the response analysis. Since this method was first developed in the 1980s, many transform methods in the time domain have been proposed and improved to overcome difficulties in various frequency dependencies in IFs (Wolf & Motosaka, 1989;Meek, 1990;Motosaka & Nagano, 1992;Hayashi & Katsukura, 1990). Nakamura (2006a;2006b;2008a;2008b) has developed various sophisticated transform methods that can deal with strong frequency dependency in IFs, non-causal impedance with large hysteretic damping, and soil nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…This method, which does not require fundamental solution, has been successfully used in coupling with ÿnite elements and applied for three-dimensional soil-structure interactions in the time domain. Another method is the one using the transformation of the dynamic sti ness matrix into the terms in time the domain [16]. However, the dynamic sti ness matrix for the far-ÿeld region is usually obtained numerically at each frequency.…”
Section: Introductionmentioning
confidence: 99%